DIRECT MEASUREMENTS OF SKIN, EYE LENS AND THYROID DOSE DURING PEDIATRIC BRAIN CT EXAMINATIONS. Issue 3 (13th November 2017) - Ploussi, Agapi; Stathopoulos, Ioannis; Syrgiamiotis, Vasileios; Makri, Triantafillia; Hatzigiorgi, Christiana; Platoni, Kalliopi; Carinou, Eleftheria; Efstathopoulos, Efstathios P
Abstract: Pediatric brain computed tomography (CT) is identified as the most frequent CT examination in children. The aim of the study is the direct measurement of skin, eye lens and thyroid dose in pediatric patients during brain CT examinations. The study included 35 pediatric patients who underwent brain CT examinations. The patients were categorized in three age groups: Group A (age range: 0.8–1 years), Group B (age range: 2.0–4.9 years) and Group C (age range: 5.5–15.5 years). thermoluminescent dosimeters (TLDs) were placed on the eyes, the frontal region of the head, the mastoid apophysis and the thyroid gland. The skin dose was found 16.6 ± 1.5, 38.8 ± 5.1 and 41.7 ± 9.4 mGy for Groups A, B and C, respectively. The mean dose for the eye lens was 10.5 ± 3.3, 29.9 ± 8.6 and 34.2 ± 14.9 mGy and for the thyroid 1.7 ± 0.4, 2.4 ± 0.5 and 1.9 ± 0.4 mGy for Groups A, B and C, respectively. In vivo dosimetry using TLDs proved to be an efficient method. Gantry tilting and patient's set-up seem to significantly affect eye lens dose.